2020
DOI: 10.1128/aem.01835-20
|View full text |Cite
|
Sign up to set email alerts
|

The Heterotrophic Bacterium Cupriavidus pinatubonensis JMP134 Oxidizes Sulfide to Sulfate with Thiosulfate as a Key Intermediate

Abstract: Heterotrophic bacteria actively participate in the biogeochemical cycle of sulfur on Earth. The heterotrophic bacterium Cupriavidus pinatubonensis JMP134 contains several enzymes involved in sulfur oxidation, but how these enzymes work together to oxidize sulfide in the bacterium has not been studied. Using gene-deletion and whole cell assays, we determined that the bacterium uses sulfide:quinone oxidoreductase to oxidize sulfide to polysulfide, which is further oxidized to sulfite by persulfide dioxygenase. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 55 publications
0
25
0
Order By: Relevance
“…when sulfane sulfur level is high, cysteine residues are sulfhydrated to form RS n H (n≥2) or RS n R (n≥3) bond, which leads configuration change of the regulator and subsequently high expression of PDO and other genes, and then sulfane sulfur level is decreased through oxidizing to sulfite (19). Therefore, Group I regulators mainly 21 function as managers to maintain the homeostasis of intracellular sulfane sulfur.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…when sulfane sulfur level is high, cysteine residues are sulfhydrated to form RS n H (n≥2) or RS n R (n≥3) bond, which leads configuration change of the regulator and subsequently high expression of PDO and other genes, and then sulfane sulfur level is decreased through oxidizing to sulfite (19). Therefore, Group I regulators mainly 21 function as managers to maintain the homeostasis of intracellular sulfane sulfur.…”
Section: Discussionmentioning
confidence: 99%
“…In the latest two decades, intensive studies of sulfane sulfur have been performed with mammalian cells because it is found that sulfane sulfur is involved in the regulation of diverse physiological and pathological processes including apoptosis, carcinogenesis, and redox maintenance (15)(16)(17)(18). On the other hand, studies of microorganism sulfane sulfur are traditionally focused on its metabolism and its role in the global sulfur cycle (19,20). In recent years, the physiological functions of sulfane sulfur in microorganisms also attract attentions.…”
Section: Introductionmentioning
confidence: 99%
“…Thiosulfate is spontaneously produced by reacting sulfite with elemental sulfur [ 1 ], and it is a key intermediate in the biogeochemical cycle of sulfur [ 2 ]. Many heterotrophic bacteria oxidize H 2 S to thiosulfate as a detoxification mechanism [ 3 , 4 , 5 ], and other bacteria oxidize thiosulfate to sulfate to gain energy for growth [ 6 , 7 , 8 ]. Further, bacteria and yeast readily use thiosulfate as a sulfur source for growth [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…As previously reported, the sulfide oxidation rates of eight heterotrophic bacteria ranged from 0.1 to 50 µmol·min −1 ·g −1 dry cell mass, showing that the rates of sulfide removal are comparable to those of chemoautotrophic bacteria (Hou et al 2018 ). Therefore, the heterotrophic bacteria capable of rapidly oxidizing sulfide offer an alternative for sulfide biotreatment (Xia et al 2017 ; Xin et al 2020 ). Sulfide: quinone oxidoreductase (Sqr) and flavocytochrome c sulfide dehydrogenase (FCSD) are two different enzymes with sulfide oxidation activity in the periplasmic and cytosolic sides of the membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Sqrs are classified into six types based on the structural analysis (Marcia et al 2010 ). Subsequently, persulfide dioxygenase (Pdo) further oxidizes sulfane sulfur to sulfite and is found in Cupriavidus pinatubonensis JMP134 (Xin et al 2020 ). Some heterotrophic bacteria contained only Sqr, while others contained both Sqr and Pdo, and they were able to oxidize sulfide (Gao et al 2017 ; Xia et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%